"STRATEGY OF ACTIONS" FOR 2017-2021 YEARS: STRUCTURAL CHANGES IN NEW ECONOMIC HISTORY OF UZBEKISTAN - DSc Valiyev Bobur Batirovich (Western European Studies, 2024)
The article is about the discovery of the new history of structural changes, achievements and economic results and the implementation of the "Strategy of actions" in 2017-2021. Annual economic development, changes in state economic policy, provision of human interests, production relations reforms are illuminated
Keywords: Uzbekistan; economic history; Strategy of actions